Analisis Tingkat Kesehatan Bank Syariah Di Indonesia - Wahyudi, Jihad; Bambang (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to examine the health level of Islamic banks in Indonesia. Profitability ratio is measured by operating expenses to operating income (BOPO), return on assets (ROA), and return on equity (ROE), Liquidity ratio is measured by cash ratio and financing to deposit ratio (FDR), solvency ratio is measured by capital adequacy ratio (CAR). This type of research is descriptive quantitative. The research population is Islamic banks listed on the Indonesia Stock Exchange (IDX). The sample of this study was obtained using purposive sampling method, which is a sample selection method using certain criteria. Based on the purposive sampling method, 4 samples were obtained from a total of 4 Islamic banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2022-2024. The data analysis technique used is ratio calculation using the Microsoft Excel 2010 program. Based on the results of testing and calculations, it was found that 1 out of a total of 4 companies was considered unhealthy in the BOPO method. 2 out of 4 companies are declared unhealthy in the ROA calculation method. The four samples are declared unhealthy in the ROE calculation method. The four samples are declared healthy in the cash ratio calculation method. 2 out of 4 companies are declared unhealthy in the FDR calculation method. All four samples are declared healthy in the CAR method.